To the issue of legal regulation of personal light electric transport - Dzyubanovskyi, Yurii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article is devoted to the study of the issue of legal regulation of personal light electric transport. The current state of the road situation and the need to use light electric transport are analyzed. The problem of a gap in the legislation regarding the legal regulation of PLE, which leads to criminal legal consequences, is highlighted. The legislation of Ukraine and its peculiarities regarding the regulation of social relations related to the use of personal light electric transport are studied. Attention is drawn to the need to improve the legislative system of Ukraine, in particular, regarding the status of PLE and the characteristics of its user. The draft law registered in the Verkhovna Rada of Ukraine on amendments to some legislative acts on improving the regulation of relations in the field of ensuring the safety of certain categories of road users (users of personal light electric vehicles, cyclists and pedestrians), which is supposed to regulate certain issues of the status of PLE and its users, is analyzed. The concept of PLE and the user of PLE are considered. The rights and obligations of the user of a personal light electric vehicle are analyzed. Recommendations are given to improve the legislation in this direction, in particular, regarding the expansion of the list of PLE user rights. The issue of introducing into legal circulation a personal light electric vehicle and a PLE user is under consideration. An opinion is expressed regarding the expediency of replacing the concept of PLE user with driver. The issue of the latter's responsibility for violating traffic rules is being investigated. Recommendations are provided for improving national legislation in the field of legal regulation of the use of personal light electric vehicles.